2014
DOI: 10.4322/cto.2014.035
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing disorders among substance dependents

Abstract: Purpose: (1) To compare sensory processing patterns as expressed in daily life between substance dependents and typical controls; (2) profile the prevalence of sensory processing disorders (SPD) among substance dependents; and (3) examine gender effect on SPD within and between groups. Methods: Two hundred ninety people aged 19-64 participated in this study. The study group included 145 individuals who lived in the community or took part in an outpatient program because of addiction to drugs/alcohol and had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…These atypical results are consistent with those of an adult South African substance-using sample, 3 and with multiple studies examining the sensory processing patterns associated with a range of mental and physical health conditions. 1 , 2 , 9 , 11 , 15 20 , 40 , 41…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These atypical results are consistent with those of an adult South African substance-using sample, 3 and with multiple studies examining the sensory processing patterns associated with a range of mental and physical health conditions. 1 , 2 , 9 , 11 , 15 20 , 40 , 41…”
Section: Discussionmentioning
confidence: 99%
“…Chi-squared (χ 2 ) tests of goodness of fit were run to measure associations between categorical variables. Because gender has been significant in earlier studies, 2 preliminary independent samples t -tests were conducted for gender with continuous study variables, and chi-squared (χ 2 ) tests of goodness of fit for gender and categorical variables. Associations between ordinal scale variables were assessed using Spearman's r correlation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its clinical manifestations are characterized by sensory under-responsivity (SMD-SUR), demonstrated by disregarded or delayed responses to stimulation; and sensory over-responsivity (SMD-SOR), perceiving non-painful sensations as irritating, unpleasant [ 25 , 27 ], or painful [ 28 , 29 , 30 ]. The sensory realm has been neglected over the years [ 31 ], and only recently, initial findings indicate SMD in SUD [ 32 , 33 , 34 , 35 , 36 ]. Importantly, our recent work found that 54% of individuals with SUD were also identified as having SMD; specifically, 47% were identified with SMD-SOR [ 32 ].…”
Section: Introductionmentioning
confidence: 99%